Website E-Commerce dan E-Auction - Natanael, Christian Hadikusuma; Wibowo, Adi; Yulia, Yulia (Jurnal Infra, 2015)
The development of information technology has created new business opportunities. One of them is online buying and selling. Online buying and selling activities also begin to diverse, besides direct selling where buyer pays the price of goods that specified by the seller, the auction system where prospective buyers are competing against each other to give the highest bid for the items auctioned within a certain period is starting to emerge. but a growing number of online buying and selling activities also provide opportunities for sellers and prospective buyers to cheat and create violations in online buying and selling activities.The creation of this E-commerce and E-auction Website can help sellers sell their goods and make it easy for prospective buyers to search and buy desired goods. In this website, sellers are also able to sell goods with auction system. To prevent violations, there is a deposit system for auction bidders and escrow system where the website administrator acting as a third party for payment intermediary. This website is developed with PHP, HTML, and javascript programming language. Database used is MySql. The code is written using brackets.The creation of product category taxonomy is done by reviewing product category taxonomies of several similar websites and combined based on questionnaire result. Checking and closing of auctions done by creating script which run automatically and scheduled with windows scheduler. This this E-commerce and E-auction Website provides place for online selling and buying activities with direct selling system and auction system. This website also provide escrow service for payment which can improve transaction security.